Modelling of Carbon Capture Process for Coal-Fired Power Plants in Indonesia - Sanggono Adisasmito; Anggit Raksajati; Alfin Ali; Henry Susilo; Muhammad Arif Susetyo; Alfian Muhammad Reza (Chemical Engineering Transactions, 2023)
The high consumption of coal in the power generation sector results in high greenhouse gas (GHG) emissions in Indonesia. Indonesian Government still needs to reduce its GHG emissions to below 662 MtCO2e in order to meet the Intergovernmental Panel on Climate Change (IPCC) scenario. This condition encourages the government to develop a strategy for decarbonization as stated in the Long-term Strategy on Low Carbon and Climate Resilience 2050 document. The retrofitting potential of Indonesian coal power plant was evaluated. Several factors such as Levelized Cost of Electricity (LCoE), CO2 emission intensity prior to capture, energy penalty, and the presence of installed flue gas desulfurizer (FGD) were used as determining parameters in selecting priority power plants to be retrofitted. The mass and energy balance of the CCS process was modelled using Aspen HYSYS V12. Based on simulation and techno-economic calculations results, it can be concluded that the LCoE value of CCS-retrofitted coal-fired power plants are influenced by the plant's capacity and the existence of FGD units. The implementation of CCS technology through retrofitting in Indonesia shall be prioritized for 1,000 MW ultra-supercritical power plants that already have existing seawater FGD technology. The increase in costs, together with a decrease in power production, results in an increase in LCoE values of up to USD 0.11/kWh for 1,000 MW power plants. This result is expected to be used as a consideration for the Indonesian government in mapping out a decarbonization strategy in the energy generation sector.